Penerapan Metode Transportasi untuk Optimalisasi Distribusi pada UMKM Rejeki Lumintu - Freeco Rantika, Rizka; Maysaroh, Sindi; Dwi Puspitasari, Ririn; Adi Prasetyo, Candra; Purwaningrum, Titis (Teewan Journal Solutions, 2025)
This study aims to optimize the distribution of goods from three warehouses to three branches (Lamongan, Madura, and Surabaya) at UMKM Rejeki Lumintu by utilizing the transportation method. The objective is to minimize transportation costs while ensuring demand fulfillment at each branch. Ensuring the minimum total transportation cost. Notably, the distribution to Madura proves to be the most cost-efficient compared to other branches. This study demonstrates the effectiveness of the transportation method in achieving cost efficiency and operational reliability in distribution management. These solutions are then evaluated using the Modified Distribution Method (MODI), yielding a total Rp 22.130.000.